An Efficient Surface Mapping Technique Using Laser Triangulation For Image Reconstruction - Tjio, Hok Hoo (2003)
An image acquisition system, which is used to capture 2-D images of object/scene for 3-D image reconstruction, is developed based on triangulation technique. The system consists of three devices, i.e. B/W CCO camera, laser diode and rotary table. These devices are placed in such a way that a triangle is formed. A grating line, which has a width of one pixel, is mounted in front of the laser diode. The purpose of the grating line is to project a stripe line on the surface of the object/scene. In this research, the positions of the camera and the laser diode are fixed. In order to acquire sufficient information for 3-D image reconstruction, the object/scene is rotated 360° about the azimuth of the rotary table. At every 15°, the rotary table is paused and a reflected image of the object is captured by the camera. Therefore, 24 different images are recorded in one complete rotation.